{{ item.displayTitle }}

No history yet!

Student

Teacher

{{ item.displayTitle }}

{{ item.subject.displayTitle }}

{{ searchError }}

{{ courseTrack.displayTitle }} {{ statistics.percent }}% Sign in to view progress

{{ printedBook.courseTrack.name }} {{ printedBook.name }} a

When solving a system of equations using substitution, there are three steps.

- Isolate a variable in one of the equations.
- Substitute the expression for that variable into the other equation and solve.
- Substitute this solution into one of the equations and solve for the value of the other variable.

$2x+4y=14$

Substitute$x=-8+3y$

$2(-8+3y)+4y=14$

DistrDistribute $2$

$-16+6y+4y=14$

AddTermsAdd terms

$-16+10y=14$

AddEqn$LHS+16=RHS+16$

$10y=30$

DivEqn$LHS/10=RHS/10$

$y=3$

b

$-3x+y=-2$

Substitute$y=-5+2x$

$-3x+(-5+2x)=-2$

RemoveParRemove parentheses

$-3x−5+2x=-2$

AddTermsAdd terms

$-x−5=-2$

AddEqn$LHS+5=RHS+5$

$-x=3$

DivEqn$LHS/-1=RHS/-1$

$x=-3$

c

$2x−2y=18$

Substitute$x=5−y$

$2(5−y)−2y=18$

DistrDistribute $2$

$10−2y−2y=18$

SubTermSubtract term

$10−4y=18$

SubEqn$LHS−10=RHS−10$

$-4y=8$

DivEqn$LHS/-4=RHS/-4$

$y=-2$